Investigating the influence of flow rate on biofilm growth in three dimensions using microimaging. (July 2018) - Ostvar, Sassan; Iltis, Gabriel; Davit, Yohan; Schlüter, Steffen; Andersson, Linnéa; Wood, Brian D.; Wildenschild, Dorthe
Highlights: A study of the effects of flow rate on three-dimensional growth of biofilm in porous media was conducted using x-ray microtomography. Generally, we observed 1 to 2 orders of magnitude decrease in permeability as a result of bioclogging for all flow rates and all columns. A combination of results from different measurements all suggest that biofilm growth was oxygen limited at the lowest flow rate, and affected by shear stresses at the highest flow rate. The approach opens the way to more systematic studies of the structure-function relationships involved in biofilm growth in porous media and the impact that such growth may have on physical properties such as hydraulic conductivity. Abstract: We explore how X-ray computed microtomography can be used to generate highly-resolved 3D biofilm datasets on length scales that span multiple pore bodies. The data is integrated into a study of the effects of flow rate on three-dimensional growth of biofilm in porous media. Three flow rates were investigated in model packed-bed columns. Biofilm growth was monitored during an 11-day growth period using a combination of differential pressure and effluent dissolved oxygen measurements. At the end of the growth period, all columns were scanned using X-ray computed microtomography and a barium sulfate-based contrast agent. The resulting images were prepared for quantitative analysis using a novel image processing workflow that was tailored to this specific system. The reduction in permeability due to biofilm growth was studied using both transducer-based pressure drop measurements and image-based calculations using the Kozeny–Carman model. In addition, a set of structural measures related to the spatial distribution of biofilms were computed and analyzed for the different flow rates. We generally observed 1 to 2 orders of magnitude decrease in permeability as a result of bioclogging for all columns (i.e, across flow rates). The greatest average permeability and porosity reduction was observed for the intermediate flow rate (4.5 ml/h). A combination of results from different measurements all suggest that biofilm growth was oxygen limited at the lowest flow rate, and affected by shear stresses at the highest flow rate. We hypothesize that the interplay between these two factors drives the spatial distribution and quantity of biofilm growth in the class of porous media studied here. Our approach opens the way to more systematic studies of the structure-function relationships involved in biofilm growth in porous media and the impact that such growth may have on physical properties such as hydraulic conductivity.